European Monetary Unification - Eichengreen, Barry (Journal of Economic Literature, 1993)
Work on this paper was begun during visits to the International Finance Division of the Board of Governors of the Federal Reserve System and the Research Department of the International Monetary Fund and completed during visits to the Bank of France and the Institute for Advanced Study in Berlin. I gratefully acknowledge the support and hospitality of all these institutions while absolving them of responsibility for the views expressed here. Research assistance was provided by Ansgar Rumler andfinancial support by the Center for German and European Studies of the University of California. For comments on portions of this work I thank Tamin Bayoumi, Lorenzo Bini-Smaghi, Paul De Grauwe, Jeffry Frieden, Alexander Italianer, Peter Kenen, Paul Masson, Thomas Mayer, Ronald McKinnon, Jacques Melitz, Richard Portes, Gianni Toniolo, Jiirgen von Hagen, and Charles Wyplosz.